К вопросу о возрастном развитии выдры острова Сахалин - Беньковский, Л.М. (Вестник зоологии, 1975)
On the basis of anatomo-morphological investigations of 85 otter males and fe- males as well as on the basis of catches and tagging the following periods were established in the postnatal development of otter: suckling (from birth to 6-7 months), sexual maturity (from 2-2.5 to 6-7 years) and attenuation of the begetting power and senescence (after 6-7 years). For all periods of otter development the dimensional, weight and interior peculiarities are typical for the otter testifying to the fact that sexual and age dimorphism is well pronounced in the animals for all their life.